#TITLE_ALTERNATIVE# - SETIYO PRABOWO (NIM: 23607031); Tim Pembimbing : Dr. Hisar M. Pasaribu; Dr. Toto Indriyanto, ACHMAD
WiSE-8 aircraft operates close to on sea surface, which required a specific navigation system designed to match the operational requirement of the aircraft. Therefore, in this thesis will study, design and develop a prototype of terrestrial navigation system. A development of the navigation system simulator, is also carried out for demonstration purpose. In this research a literature study is performed as basis for and designs the WiSE-8 navigation system. Several possible navigation systems are considered, for example GPS, VOR, NDB and DF. Based on the literature study the solution DF system is selected for WiSE-8. DF system can generate information in the form of relative of bearing to 2 transmitter halting points. This information can be processed by applying theta-theta formulation , so that it can display the aircraft position is 2 dimension platform. This research also study about the location of DF transmitter at several routes are extensively studied, e.g : Dumai-Batam, Semarang-Karimunjawa and Kupang-Larantuka. It consider the transmitter and receiver DF specification. The result can be used for other WiSE-8 routes. The research produces a WiSE-8 navigation system prototype such as Bearing Generator, Bearing Display and DF Display. The prototype has 1 o relative bearing accuracy.